Clinical Characteristics of Patients With Benign Paroxysmal Positional Vertigo Diagnosed Based on the Diagnostic Criteria of the Bárány Society - Ling, Xia; Zhao, Dan-Hua; Shen, Bo; Si, Li-Hong; Li, Kang-Zhi; Hong, Yuan; Li, Zhe-Yuan; Yang, Xu (Frontiers in Neurology, 2020)
Objectives: To analyze the clinical characteristics of patients with benign paroxysmal positional vertigo (BPPV) diagnosed based on the diagnostic criteria of Bárány Society, verify the clinical application value of the diagnostic criteria, and further explore the clinical problems associated with the diagnosis of possible BPPV. Methods: A total of 481 patients with BPPV who were admitted from March 2016 to February 2019 were included. All patients were diagnosed by the Dix-Hallpike, straight head hanging and supine roll tests, the nystagmus was recorded using videonystagmography. For patients with possible BPPV (uncertain diagnosis), particle repositioning therapy and follow-up diagnosis were used to further clarify diagnosis. Results: Based on Bárány Society's diagnostic criteria for BPPV, the distribution characteristics of different BPPV types were as follows: 159 (33.1%) patients had posterior canal BPPV-canalolithiasis (PC-BPPV-ca), 70 (14.6%) patients had horizontal canal BPPV-ca (HC-BPPV-ca), 55 (11.4%) patients had spontaneously resolved-probable-BPPV (Pro-BPPV), and 53 (11.0%) patients had HC-BPPV-cupulolithiasis (HC-BPPV-cu). In emerging and controversial BPPV, 51 (10.6%) patients had multiple canal BPPV (MC-BPPV), 30 (6.2%) patients had PC-BPPV-cu, and 19 (4.0%) patients had anterior canal BPPV-ca (AC-BPPV-ca), 44 (9.1%) patients had possible-BPPV (Pos-BPPV). Among the 44 patients with Pos-BPPV, 23 patients showed dizziness/vertigo without nystagmus during the initial positional test, five patients were possible MC-BPPV, four patients had persistent geotropic positional nystagmus lasting > 1 min when lying on both sides, and were considered to have Pos-HC-BPPV, four patients showed apogeotropic nystagmus when lying on one side, and were considered to have possible short-arm HC-BPPV, four patients showed geotropic nystagmus when lying on one side, and were considered to have Pos-HC-BPPV, three patients had down-beating nystagmus, lasing > 1 min, were considered to have Pos-AC-BPPV-cu. One patient showed transient apogeotropic positional nystagmus on both sides during the supine roll test, and was diagnosed with possible anterior arm HC BPPV. Conclusions: PC-BPPV-ca is the most common among patients with BPPV, followed by HC-BPPV-ca. In emerging and controversial BPPV, MC-BPPV and Pos-BPPV were more common. For the diagnosis of Pos-BPPV, a combination of the history of typical BPPV, particle repositioning therapy and follow-up outcome is helpful to clarify the diagnosis.